The effect of sport-specific virtual reality training for soccer players on cognitive performance and related brain processing - Casella, A.; Panacci, C.; Filosa, M.; Aydin, M.; Boccacci, L.; Di Russo, F. (Journal of Sports Sciences, 2026)
This study aimed to evaluate the effects of sport-specific training in virtual reality (VR) on perceptual and cognitive abilities and their neurophysiological correlates in young soccer players. Twenty-four young semi-elite soccer athletes were assigned to an experimental (Exp) or control (Ctr) group. Participants` cognitive functions were tested before and after an 8-week standard soccer training using a visuomotor cognitive task during electrophysiological (EEG) recordings. The Exp group in the last 30 minutes of each training session performed the VR training aimed at improving processing speed, cognitive flexibility, and working memory. While the cognitive task allowed to measure response speed and accuracy, the EEG permitted to measure the event-related potential (ERP) evoked by the cognitive task. Results showed that both response speed and accuracy were improved in the Exp group only, and this effect could be explained by increased sensorimotor integration in prefrontal areas indexed by the prefrontal P1 (pP1) component and increased post-perceptual cognitive processing as decision-making in parietal areas indexed by the P3 component. These results support the effectiveness of VR in enhancing cognitive functions, highlighting the technology`s potential for innovative training for soccer.